PENERAPAN ASAS KELANGSUNGAN USAHA (BUSINESS GOING CONCERN) DALAM SISTEM HUKUM KEPAILITAN INDONESIA: Application of the Business Going Concern Principle in the Indonesian Bankruptcy Law System - Manangi, Izra Charistulus; Wicaksana, Arif (AMICUS CURIAE, 2024)
One of the four principles stipulated by Law Number 37 of 2004 concerning Bankruptcy and Suspension of Obligations for Debt Payment is the Business Continuity Principle. The concept of business continuity which is also called "Business Going Concern" focuses on the continued existence of the debtor company, so that it is hoped that bankruptcy will not occur. The problem is how to implement Law Number 37 of 2004 concerning the Principles of Business Continuity; Meanwhile, data processing was carried out qualitatively, normative research was carried out to find answers to these problems, and deductive methods were used to draw conclusions. The existing analysis results in the conclusion that Article 179 to Article 184 of Law Number 37 of 2004 justifies the application of the Business Continuity Principle.